A Nurses' Palliative Care Knowledge and Attitudes: Psychosocial and Spiritual as Aspects That Need to Be Improved - Doni tri wijayanto; Isna Hikmawati; Umi Solikhah; Happy Dwi Aprilina (Sarana Ilmu Indonesia (Salnesia), 2026)
Palliative care is a healthcare service that emphasizes addressing the holistic needs of patients, including physical, psychological, psychosocial, and spiritual aspects, particularly for those with chronic illnesses or life-threatening conditions. Nevertheless, its implementation in healthcare facilities continued to face challenges, especially regarding the limited availability of palliative services and the insufficient knowledge among nurses, who play a pivotal role in delivering care. This study aimed to examine the relationship between nurses’ knowledge and attitudes toward palliative care in inpatient wards. The study employed a quantitative approach with a descriptive-analytical cross-sectional design. All nurses meeting the inclusion criteria were recruited as subjects through total sampling, resulting in a sample of 54 participants at Purwokerto Islamic Hospital. Data were collected using the Palliative Care Quiz for Nursing (PCQN-I) to assess knowledge and the Frommelt Attitudes Toward Care of the Dying (FATCOD-B)scale to evaluate attitudes. Data analysis was conducted using Spearman’s rank correlation test, yielding a p-value of 0.001 (p < 0.05) and a correlation coefficient of 0.610, indicating a moderately strong positive relationship, which demonstrates that nurses’ knowledge is associated with their attitudes toward palliative care. These findings suggested that enhancing nurses’ knowledge contributes to the development of more positive attitudes. Therefore, it remained essential to strengthen nurses’ competencies, particularly in the psychosocial and spiritual domains.